THE KINETICS OF THE OXIDATION OF PYRITE BY FERRIC IONS AND DISSOLVED OXYGEN: AN ELECTROCHEMICAL STUDY - EXPERIMENTAL OXIDATION OF PYRITE - Holmes P.R.; Crundwell F.K. (My University, 2000)
The dissolution of pyrite is important in the geochemical cycling of iron and sulphur, in the formation of acid mine drainage, and in the extraction of metals by bacterial leaching. Many researchers have studied the kinetics of dissolution, and the rate of dissolution has often been found to be half-order in ferric ions or oxygen. Previous work has not adequately explained the kinetics of dissolution of pyrite. The dissolution of pyrite is an oxidation-reduction reaction. The kinetics of the oxidation and reduction half-reactions was studied independently using electrochemical techniques of voltammetry. The kinetics of the overall reaction was studied by the electrochemical technique of potentiometry, which consisted of measuring the mixed potential of a sample of corroding pyrite in solutions of different compositions. The kinetics of the half reactions are related to the kinetics of the overall dissolution reaction by the condition that there is no accumulation of charge. This principle is used to derive expressions for the mixed potential and the rate of dissolution, which successfully describe the mixed potential measurements and the kinetics of dissolution reported in the literature. It is shown that the observations of half-order kinetics and that the oxygen in the sulphate product arises from water are both a direct consequence of the electrochemical mechanism. Thus it is concluded that the electrochemical reaction steps occurring at the mineral-solution interface control the rate of dissolution. Raman spectroscopy was used to analyze reaction products formed on the pyrite surface. The results indicated that small amounts of polysulphides form on the surface of the pyrite. However, it was also found that the mixed (corrosion) potential does not change over a 14-day leaching period. This indicates that even though polysulphide material is present on the surface, it does not influence the rate of the reactions occurring at the surface. Measurements of the sulphur yields as a function of electrode potential indicate that thiosulphate is not the only source of the sulphur product.